THE EPILOGUE OF DENNIS LEHANE’S MYSTIC RIVER: A SYNTACTIC ANALYSIS - Wedhowerti, Wedhowerti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The study aims to analyze the epilogue of Lehane’s Mystic River. It employs syntactic approach, and it is qualitative in nature. Departing from the fact that novel is considered as a form of creative writing, syntax with its syntactic analysis then enables the researcher to go deeper into the epilogue of Lehane’s to understand its creative use of language. The five sentences in the epilogue are studied to find out how Lehane produces his clause types and thematic relations in his novel. The results yield the five sentences in the epilogue are all finite clauses for they have a finite verb in each. In terms of thematic relations, each verb in the five sentences of Lehane’s epilogue assigns different thematic roles. Each verb has different lexical representation. Verb come in Datum 1 assigns Agent and Source. Verb pull in Datum 2 assigns Agent and Theme. Verb look in Datum 3 assigns Agent and Location. Meanwhile Datum 4 has two thematic roles (Theme and Location). Datum 4 has no Agent in it. Verb block in Datum 5 assigns Agent, Theme, and Location. The four thematic roles have different state of percentage where Agent occupies the highest number of 36.36%. It is followed by both Theme and Location of 27.27% respectively. Source, in contrary, has the lowest number of 9.09%.